TNF receptors are associated with tau pathology and conversion to Alzheimer’s dementia in subjects with mild cognitive impairment - Zhao, Aonan; Li, Yuanyuan; Deng, Yulei (Neuroscience letters, 2020)
•higher CSF levels of TNF-α related inflammatory proteins in the MCI and AD patients with positive tau pathology.•TNF receptors were associated with t-tau and p-tau, other than Aβ1-42, in HC, MCI and AD subjects.•TNF receptors are potential early predictors for the MCI-to-AD conversion. Tumor necrosis factor-a (TNF-α) signaling pathway plays a significant role in Alzheimer’s disease (AD). This study aimed to explore the relationship between TNF-α related inflammatory proteins and pathological markers of AD, and examine their possibility as a predictor of the conversion of mild cognitive impairment (MCI) to AD. This study included both cross-sectional and longitudinal designs. The levels of TNF-α related inflammatory proteins, Aβ1-42, total-tau(t-tau), phosphorylated tau (p-tau) from cerebrospinal fluid (CSF) were analyzed in healthy controls (HC, n = 90), MCI (n = 116), and AD participants (n = 75) from the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Kaplan-Meier analyses were used to evaluate the predictive value of the examined putative AD markers after follow-up visits. In the cross-sectional cohort, we observed higher CSF levels of TNF-α related inflammatory proteins in the MCI and AD patients with positive tau pathology. TNF receptors (TNFR) were more closely associated with t-tau and p-tau than Aβ1-42, in HC, MCI and AD subjects. In the longitudinal cohort with a mean follow-up of 30.2 months, MCI patients with high levels of CSF TNFR1 (p = 0.001) and low levels of TNFR2 (p < 0.001) were more likely to develop into AD. TNFR-signaling might be involved in the early pathogenesis of AD and TNF receptors may serve as potential predictive biomarkers for MCI.